Pengaruh Pendapatan Asli Daerah (Pad),Dana Alokasi Umum (Dau) ,Dana Alokasi Khusus (Dak) Dan Dana Bagi Hasil (Dbh) Terhadap Pertumbuhan Ekonomi Daerah Dengan Belanja Daerah Sebagai Variabel Moderating Pada Kabupaten Dan Kota Di Provinsi Jawa Tengah Tahun 2010-2014 - , Saleh, Fatchan Achyani, SE, M.Si., Dr. r. (2017)
This research aimed to find out the effect of Local Revenue, General Allocation Funds, Special Allocation Funds and Profit Sharing Funds to local economic growth with Local Expenditure as moderating variable in district and urban on Province of Central Java from 2010 to 2014. The type of data in this research is secondary data which collected from the report document realization of Local Government Revenues and Expenditures (APBD) district or urban on Province of Central Java and variable of PDRB from Statistic Indonesia (BPS) of Central Java from 2010 to 2014. The population in this research is all the distric or urban on Province of Central Java and the research sample was determined by the method of purposive sampling. The result of this research shows that The Local Revenue, General Allocation Funds and Special Allocation Funds has influence on local economic growth, but The Profit Sharing Funds has no influence on local economic growth. The Local Revenue has influence on local economic growth with Local Expenditure as moderating variabel, but General Allocation Funds, Special Allocation Funds and Profit Sharing Funds has no influence on local economic growth with Local Expenditure as moderating variabel. Keywords: Local Revenue, General Allocation Funds, Special Allocation Funds,Profit Sharing Funds, Local Expenditure ,Economic Growth